Nutrient Recovery and Recycling from Human Urine: A Circular Perspective on Sanitation and Food Security. (2016) - Ganesapillai, M.; Simha, Prithvi; Gupta, Kunal; Jayan, Mahesh
Abstract: Closed-loop nutrient cycling is a simple, persuasive and elegant approach to realize efficient natural resource management, improved human well-being and long-term food security. In the spirit of sustainable sanitation through nutrient cycling, this study proposes a new pathway to realize resource recovery from anthropogenic waste fractions by the application of physico-chemical separation processes. Microwave Activated Carbon (MAC) prepared from coconut shells (agro-waste) were immobilized on etched glass bead supports and utilized within a continuous flow packed-bed column. Physical adsorption experiments were performed by passing human urine through the column to strip and recover more than 80% of the intrinsic urea. Backwashing of the column was performed to demonstrate the ease of urea-N desorption, reusability of MAC over multiple cycles and the reversible nature of the process. Further nutrient recovery was realized by dephosphatizing the column overflow with MgO to allow phosphate precipitation (>90%) as struvite. Sorption kinetics, behaviour and influence of process parameters were studied by testing the experimental data against Yoon-Nelson, Thomas and Adams-Bohart models. The column adsorption was also numerically optimized using Response Surface Methodology to determine the optimal parameters as: sorbate flow rate – 8.5 L.h -1, urea concentration – 100%, support size – 1 cm and consequently, column capacity of 21.58 g. Nutrient recovery, concentration and recycling from diverted human urine can be seen as a synergistic and circular solution to the issues of sanitation, hygiene, water, and food security.